Straw input can parallelly influence the bacterial and chemical characteristics of maize rhizosphere. Issue 1 (1st January 2020) - Li, Rong; Liu, Jun; Li, Jiani; Sun, Caixia
ABSTRACT: The effects of straw input, including three strategies: chopped straw, straw-derived compost and biochar, on bacterial communities and chemical composition in maize rhizosphere were investigated according to a three-year field experiment. Illumina MiSeq sequencing showed that biochar input increased bacterial richness but decreased bacterial diversity in rhizosphere when compared with the results from no straw control. The functional prediction of Kyoto Encyclopedia of Genes and Genome pathways confirmed that soil subjected to straw input changed the abundance of microbiomes involved in carbohydrate metabolism significantly. Metabolomics analysis showed that straw input changed the metabolite profile of the rhizosphere soil of maize, which was most evident in the treatment of chopped-straw input. The match between the global metabolic profiles and bacterial distribution patterns was weak by performing Procrustes analysis (m 2 = 0.851, R = 0.386, P < 0.05). However, the associations between the special members of genera, predicted function involved in carbohydrate metabolism, and rhizosphere metabolites, including sugars and organic acid, were significant ( P < 0.05).